Effects of Perceptual-motor Exercises Based on Multi-sensory Therapy on Sensory Processing of Older Adults - Hossein Alibakshi; Jamil Eslami; Shima Shahrokhi; Hossein Mirzabeigi; Ensieh Naimi; Mina Sadat Mirshoja (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Aging is one of the stages of the life cycle that is accompanied by sensory changes and bodily awareness. This study aims to investigate the effectiveness of perceptual-motor exercises based on multi-sensory therapy on body image and sensory processing in elderly individuals with cognitive impairments. Methods & Materials The present study is a clinical trial with a pre-test-post-test design with an experimental and a control group, conducted in a double-blind manner. The samples were selected using the available sampling method and were randomly assigned to the control and experimental groups (15 participants in each group). The interventions were performed individually for each participant in 8 treatment sessions, 2 days a week, for a duration of 1 month. The assessment tools included the multidimensional body-self relations questionnaire (MBSRQ) and the sensory profile questionnaire. Results The results showed that the perceptual-motor exercises based on multi-sensory therapy had a significant difference in all cases of the MBSRQ (except for body satisfaction and preoccupation with excess body) and the sensory profile questionnaire in both groups (P<0.05). Additionally, the analysis of covariance in both questionnaires and in both groups was calculated to be less than 0.05 and significant. Conclusion The findings of this study showed that perceptual-motor exercises based on multi-sensory methods can improve body image and enhance sensory processing skills in elderly individuals with cognitive impairments. Therefore, educating and repeating these exercises can greatly assist therapists and clients in achieving more beneficial results.